Convergence rates in regularization for equations involving accretive operators - Bường, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
The aim of this paper is to give a theoretical analysis of convergence rates of the regularized solutions for operator equations involving m-accretive operators and of their convergence rates in combination with finite-dimensional approximations. An application to nonlinear integral equations is considered for illustration.